2022
DOI: 10.20517/jeea.2022.05
|View full text |Cite
|
Sign up to set email alerts
|

Ambient air concentrations and risk assessment of selected organochlorine pesticides (OCPs) across five Middle Eastern countries

Abstract: This paper presents data obtained from concurrently deployed polyurethane foam disk passive samplers in Kuwait, Turkey, Lebanon, Saudi Arabia, and Oman between January and October 2018. The study’s main goal was to initiate a passive air sampling network across the Middle East to generate comparable data, which will help report obligations of the various countries and be used in protocol discussions. The ∑24OCP concentrations were highest in the samples collected from Kartaba in Lebanon (7780 pg·m-3), and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Observation of the highest PBDE-66 and PBDE-85 concentrations in the group closest to the war zone support that they may be indicators of LRAT from the conflict zone to its north. Gevao et al (2022a) reported evidence for current and past usagere-volatilization of aged DDTs based on p,p'-DDE/p,p'-DDT ratio, and current usage of lindane or technical HCH considering α/γ HCH ratio across the middle east, which renders the conflict zone as a potential source area in support to the findings of this study and their LRAT potential (Wu et al, 2010).…”
Section: Comparison Of Local Emissions and Lratsupporting
confidence: 81%
See 2 more Smart Citations
“…Observation of the highest PBDE-66 and PBDE-85 concentrations in the group closest to the war zone support that they may be indicators of LRAT from the conflict zone to its north. Gevao et al (2022a) reported evidence for current and past usagere-volatilization of aged DDTs based on p,p'-DDE/p,p'-DDT ratio, and current usage of lindane or technical HCH considering α/γ HCH ratio across the middle east, which renders the conflict zone as a potential source area in support to the findings of this study and their LRAT potential (Wu et al, 2010).…”
Section: Comparison Of Local Emissions and Lratsupporting
confidence: 81%
“…The mean ∑ 9 OCP concentration in Bursa was 25.7 pg/m 3 and p,p'-DDE had the highest contribution (6.9 pg/m 3 ). Gevao et al (2022a) deployed samplers along a northwest-southeast transect across the Middle East at several sites (agricultural, industrial, remote, urban, and background) which were close to the war zone. The average ∑ 24 OCP concentrations of the subject countries were Lebanon at 1684 pg/m 3 > Turkey at 78.7 pg/m 3 > Oman at 55 pg/m 3 > Kuwait at 42 pg/m 3 > Saudi Arabia at 19.1 pg/m 3 .…”
Section: Ocpsmentioning
confidence: 99%
See 1 more Smart Citation